2017
DOI: 10.17306/j.afs.2017.0460
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of boiled breadfruit (Treculia africana) seeds did not improve hyperglycemia in streptozotocin induced diabetic rats: Effect on the oral glucose tolerance of normoglycemic rats

Abstract: Diabetes mellitus is a global health problem that is causing problems for humans around the world and becoming increasingly prevalent at an alarming rate (Aloulou et al., 2012), including amongst the rural Nigerian population. The inability of modern treatments to control all the pathophysiological aspects of diabetes, as well as the enormous cost it imposes on the economy of the developing nations of the world, ABSTRACTBackground. Although African breadfruit (Treculia africana) is said to be useful in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…Although the study by Ajiboye et al. () on T. africana fruit/seed suggested its beneficial use in the management of diabetes mellitus, our study (Eleazu et al., ) on processed T. africana seed gave contrary results, although the duration of our study was short. Furthermore, information on the effect of consumption of processed T. africana seed on the lipid profile of humans or animals is missing in literature.…”
Section: Introductioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Although the study by Ajiboye et al. () on T. africana fruit/seed suggested its beneficial use in the management of diabetes mellitus, our study (Eleazu et al., ) on processed T. africana seed gave contrary results, although the duration of our study was short. Furthermore, information on the effect of consumption of processed T. africana seed on the lipid profile of humans or animals is missing in literature.…”
Section: Introductioncontrasting
confidence: 65%
“…These findings suggest that boiling of T. africana seed impacts it with a high glycemic index. In our previous study (Eleazu et al., ), we reported that dietary intake of boiled T. africana seeds did not improve hyperglycemia in streptozotocin‐induced diabetic rats. Therefore, findings of this study suggests that the normal glucose tolerance in the groups 1 and 2 rats following oral glucose loading could be a result of the beta cells of the pancreas of the animals being able to release insulin, enhancing uptake of glucose in the insulin‐responsive tissues and not necessarily as a result of the extracts they were administered.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The increased uptake of factors like glycogen accumulation, lipogenesis, and protein synthesis are the main attributed for kidney enlargement in diabetic rats (Teoh et al., 2010). In case of increase in the liver weight, the absence of insulin production in diabetic group causes increased mobilization of fatty acids from the adipose tissue which gets accumulated in the liver and increases the weight of the organ (Eleazu et al., 2017). These results conforms that the treated diabetic groups had shown nontoxicity and had successfully prevented the enlargement of the organs in diabetic condition.…”
Section: Resultsmentioning
confidence: 99%